Unilateral Sudden Sensorineural Hearing Loss Post-Mumps: A Rare but Critical Complication Requiring Early Intervention - Purwanto, Shindi Yunia; Hanik, Siti Umi (Riviera Publishing, 2025)
Introduction: Sudden sensorineural hearing loss (SNHL) is a rare but significant complication of mumps virus infection. Although commonly self-limiting, mumps may lead to permanent auditory damage in some cases. Early recognition and treatment are crucial to improving prognosis. Case Presentation: A 14-year-old male presented with sudden left-sided hearing loss and mild tinnitus persisting for one month. He had no history of otorrhea, vertigo, allergies, or trauma. One month prior, he experienced left-sided parotid swelling for seven days, accompanied by fever, headache, malaise, myalgia, and anorexia. Examination showed normal external auditory canals and intact tympanic membranes bilaterally. Audiometry revealed severe sensorineural hearing loss in the left ear, while tympanometry showed a bilateral As curve. Nasal endoscopy identified grade I adenoid hypertrophy and mucoid secretions in the nasal turbinates. The patient was treated with nasal irrigation, methylprednisolone (3×8 mg tappering off), and mecobalamin (2×500 mg daily), with planned follow-up audiometry. Discussion: Mumps-related SNHL is estimated to occur in 1 per 20,000 cases. The pathogenesis involves cochlear damage due to viral inflammation. Audiometric findings typically indicate unilateral profound hearing loss. Corticosteroid therapy is commonly used, though efficacy in viral-induced SNHL remains uncertain. Conclusion: Mumps-related SNHL is a rare but serious complication requiring early diagnosis and management. Audiometric screening should be considered in post-mumps cases presenting with hearing complaints to prevent long-term disability. Further studies are needed to optimize treatment strategies.